2017
DOI: 10.1212/wnl.0000000000003631
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cerebral microbleeds after cranial irradiation in medulloblastoma patients

Abstract: Objective: To characterize the temporal and spatial pattern of cerebral microbleeds (CMBs) after cranial irradiation in patients with medulloblastoma. Methods:We retrospectively identified patients with medulloblastoma treated with craniospinal irradiation at the Massachusetts General Hospital between 1999 and 2015. Longitudinal MRI including T2*-weighted gradient-recalled echo (GRE) sequences were reviewed, and the prevalence, spatial pattern, and risk factors associated with CMBs were characterized.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 36 publications
(38 reference statements)
2
30
0
Order By: Relevance
“…In regard to tumor location, occipital, cerebellum, and brainstem tumors combined were associated with the highest rate of CMB development, while frontal lobe tumors were associated with increased rates of development compared with temporal and parietal lobe tumors. This finding suggests that the posterior brain and frontal lobe are the most radiosensitive brain regions in adults, agreeing well with previous findings in pediatric populations …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In regard to tumor location, occipital, cerebellum, and brainstem tumors combined were associated with the highest rate of CMB development, while frontal lobe tumors were associated with increased rates of development compared with temporal and parietal lobe tumors. This finding suggests that the posterior brain and frontal lobe are the most radiosensitive brain regions in adults, agreeing well with previous findings in pediatric populations …”
Section: Discussionsupporting
confidence: 93%
“…19 Roongpiboonsopit et al investigated the prevalence of CMBs in younger adults (median age 28.8 years) treated with whole-brain RT for a medulloblastoma; they identified CMBs in 67% (n = 18) of patients followed for a median of 4.1 years. 20 In our recent experience, in an ongoing study using the same methods as in the present study to assess CMB prevalence in adult survivors of pediatric medulloblastomas, we have so far observed a 100% cumulative incidence rate for CMB formation at follow-up times ranging between 1.1 and 15.5 years (median, 6.2 years). This supports early and accurate detection of RTinduced CMBs using advanced imaging and postprocessing methods.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with prior studies,(8) stroke from radiation vasculopathy was defined as stroke ipsilateral to the patient’s site of prior brain radiation, with no other identified mechanism of stroke. Imaging evidence of intracranial stenosis was not required for the diagnosis of radiation vasculopathy because radiation can cause small vessel vasculopathy,(21, 22) and lacunar-appearing strokes have been reported in patients after radiation. (23) Each patient’s stroke mechanism was independently adjudicated by two neurologists (NSP and JEB) with a board-certified stroke neurologist (BBN) serving as the final arbitrator.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we found a significantly higher incidence of isolated SWI blooming artifacts in metastatic melanoma patients compared with a screening cohort without BM. Additional analysis of the subgroups stratified by therapy showed that this increase could be explained by prior radiotherapy, which is a well‐known risk factor for the development of intracerebral microbleedings or cavernomas . In the case of MM, it is highly likely that these SWI lesions represent microbleedings but the possibility that such findings might be micrometastases unmasked by irradiation cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%